When the Truth Is Out There: Counseling People Who Report Anomalous Experiences - Rabeyron, Thomas (Frontiers in Psychology, 2022)
In this paper, we propose a clinical approach concerning the counseling of distressing subjective paranormal experiences, usually referred to as anomalous or exceptional experiences in the academic field. These experiences are reported by a large part of the population, yet most mental health practitioners have not received a specific training in listening constructively to these experiences. This seems all the more problematic since nearly one person in two find it difficult to integrate such experiences, which can be associated with different forms of psychological suffering. After having described briefly several clinical approaches already developed in this area, we outline the main aspects of clinical practice with people reporting exceptional experiences, in particular the characteristics of the clinician’s attitude towards the narrative of unusual events. We then present the core components of a Psychodynamic Psychotherapy focused on Anomalous Experiences (PPAE) based on three main steps: phenomenological exploration, subjective inscription and subjective integration of the anomalous experience. Such an approach, based on a non-judgmental and open listening, favor the transformation of the ontological shock that often follows the anomalous experiences into a potential source of integration and psychological transformation.